Extermination of bacteria in hide-brine curing liquors using combined alternating and direct electric current applications plus bronopol - (:unkn) unknown (ARS DOCENDI, 2015)
Microbial spoilage of hide usually results from the failure to inactivate destructive microorganisms during hide brine curing. To compensate for this problem, an effective inactivation method to be used in the leather industry was researched. Three different experiments were performed with the mixed culture of six hide bacteria to examine: 1) the effect of only bronopol on mixed culture; 2) the effect of 188 mu A/m(2) DC treatment applied together with 251 mu A/m(2) AC treatment followed by 1 g/L of bronopol on mixed culture; 3) the effect of 188 mu A/m(2) DC treatment applied alternately with 251 mu A/m(2) AC followed by a rest break of 3 h, and then renewed AC/DC application followed by addition of 1 g/L bronopol to mixed culture. The mixed cultures were completely killed with bronopol in 10 h in experiment 1. The mixed culture damaged by the electric treatments was killed by bronopol in 8 h in experiment 2. The mixed culture damaged by two cycles of the electric treatments was killed by bronopol in 3 h in experiment 3. In conclusion, combinatory usage of both two cycles of electric treatment and bronopol may be applied in hide-brine curing process to inactivate proteolytic and lipolytic bacteria.
Keywords: Electrochemical disinfection; electric current; bronopol; leather; brine curing process; bacteria; PSEUDOMONAS-AERUGINOSA BIOFILMS; GRAM-NEGATIVE BACTERIA; PACK CURED HIDES; SOAK LIQUOR; EFFICACY; SALT; IONTOPHORESIS; INACTIVATION; ANTIBIOTICS; POPULATIONS